(untitled) (Journal of Oriental Studies, 2021)
The Turkic language, called Türki, the Old Kipchak or Kipchak language, which was actively used in the Mamluk state in Egypt and the Golden Horde in the 13th-15th centuries, is the proto-language of the modern Turkic languages. Most of its lexical layer, which includes various dialects of the Turks of that period, is reflected in the lexical fund of the modern Kazakh language. The study of Mamluk-Kipchak manuscripts, written in Egypt and stored in world archives and libraries, is especially necessary for Kazakhstan Oriental studies and Turkic studies. For further comprehensive research from the point of view of language, including the vocabulary and grammar of these written monuments, stored for more than six centuries, it is necessary to determine the prerequisites for their creation, in particular, to describe the linguistic situation in society and determine the status of the Turkic language. The study is based on a comparative historical method in order to determine the status and describe the linguistic situation of the Kypchaks, who are geographically distant, but spiritually united, including linguistically. As a result, the status of the Turkic language in the Golden Horde and the Mamluk state in Egypt was determined, and the linguistic situation in the region was described. The Turks were able to preserve the language both in their homeland under the rule of the Mongol Empire, and in a foreign land in Egypt, where, along with Arabic, the Mamluks continued to use their native language and create valuable written monuments. In the Golden Horde, the Turks, gradually replacing the Mongolian language, turned from the Turkic a key language of communication both within the country and abroad, in particular, in the development of relations with Mamluk Egypt. Key words: Turki, Kipchak, Mamluk, Golden Horde, language, language situation